MOS-only design automation and a simple agile MOS-only BP/LP filter design [Salt-MOS Devre Tasarimi Otomasyonu ve Basit Bir Atik Salt-MOS BP/LP Süzgeç Tasarimi] - (:unkn) unknown (Institute of Electrical and Electronics Engineers Inc., 2017)
In this work, a systematic of the automation in the result of the re-obtained small signal parameters based on SPICE is presented for MOS-Only circuits. Accuracy of the re-obtained parameters was improved by re-formulating in the basis of SPICE and CADENCE-SPECTRE. Moreover, piece-wise polynomial regressive models are presented for gds, gm and Ids-Also, performance of the models are compared with conventional expressions. Success of the given MOS-Only design automation based on re-obtained small signal parameters is verified with an examplary new agile filter. © 2016 The Chamber of Turkish Electrical Engineers.